CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. GRAB INDONESIA DI ERA NEW NORMAL MASA PANDEMI COVID-19 - Novita Damayanti; Yuni Retna Dewi (Jurnal Pustaka Komunikasi, 2021)
Today, the social responsibility of a company or better known as CSR has become the subject of discussion among the public and business people. PT. Grab Indonesia, as an Indonesian online transportation application, together with the government, carried out a covid 19 vaccination as an implementation of CSR in the New Normal era of the Covid-19 pandemic in several regions in Indonesia for the elderly and online transportation drivers. This study aims to determine the implementation of Grab Indonesia's "vaccine for the country" Corporate Social Responsibility (CSR) during the new normal period of the covid-19 pandemic. The study uses the CSR concept from John Elkington which reveals the triple bottom line concept, namely profit, people, and planet. This research uses a case study approach. The results showed PT Grab Indonesia in the new normal era carried out CSR by holding a covid-19 vaccination together with the Ministry of Health and the Ministry of Tourism and Creative Economy and several other companies such as Fatigon, Good Doctor, Teh Pucuk as vaccine centers in Bali, Palembang, Banten, West Java and other areas.